2010
DOI: 10.1007/s00125-010-1830-9
|View full text |Cite
|
Sign up to set email alerts
|

High-fat feeding stimulates endocrine, glucose-dependent insulinotropic polypeptide (GIP)-expressing cell hyperplasia in the duodenum of Wistar rats

Abstract: Aims/hypothesis Incretins are hormones released by enteroendocrine cells in response to meals, depending upon absorption of nutrients. The present study aimed to elucidate the mechanisms through which a high-fat diet (HFD) induces insulin resistance and insulin hypersecretion by focusing on the effects on enteroendocrine cells, especially those secreting glucose-dependent insulinotropic polypeptide (GIP). Methods Forty male Wistar rats, 4 months old, were randomised into two groups; one group received a chow d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 30 publications
2
54
1
2
Order By: Relevance
“…The duodenal mucosa becomes abnormal with high fat/hexose feeding (10,(21)(22)(23)(24)(25), which in turn disturbs local nutrient absorption (26) and neuronal and hormonal signaling (24,25,27). This appears to also involve the overgrowth of certain mucosal cell types, including the K cell (10,23), which is recognized for its glucoregulatory role in secreting the incretin hormone GIP. Duodenal biopsy from humans with diabetes also shows hypertrophy, thickening, and an overgrowth of entero-endocrine cell types (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duodenal mucosa becomes abnormal with high fat/hexose feeding (10,(21)(22)(23)(24)(25), which in turn disturbs local nutrient absorption (26) and neuronal and hormonal signaling (24,25,27). This appears to also involve the overgrowth of certain mucosal cell types, including the K cell (10,23), which is recognized for its glucoregulatory role in secreting the incretin hormone GIP. Duodenal biopsy from humans with diabetes also shows hypertrophy, thickening, and an overgrowth of entero-endocrine cell types (22).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, the duodenum is the first site of fuel recognition at the time of nutrient intake. Observations in animal models and humans reveal that the duodenal mucosa exhibits abnormal hypertrophy and endocrine hyperplasia in the presence of diabetes (10). Moreover, gastrointestinal bypass procedures or device-based interventions (i.e., the endoluminal sleeve) that prevent contact between duodenal mucosa, bile, and nutrients improve insulin sensitivity (11) and b-cell function (12).…”
mentioning
confidence: 99%
“…Several studies have shown that postprandial GIP secretion was increased after chronic HF feeding (10) and in obese subjects (7). To examine the effect of 1-MO on GIP hypersecretion, mice were maintained on a semipurified HF diet for 23 wk to induce obesity, and we conducted glucose and fat loading tests.…”
Section: Effect Of 1-mo On Postprandial Blood Responses In Hf Diet-fementioning
confidence: 99%
“…A high-fat diet dramatically increases GIP secretion (6). The blood concentration of GIP is elevated in obesity (1,5,19).…”
mentioning
confidence: 99%